Improving customer service in schools based on Lean and simulation: A case study - Cabrera Paredes, Sergio Sebastian (2023)
The purpose of this research is to reduce the duration of processes and waiting times in the customer service modules of an educational institution. For this purpose, the use of the Lean Manufacturing methodology is proposed, following the framework formulated by the DMAIC sequence proposed by Lean Six Sigma, which consists of five consecutive stages: define, measure, analyze, improve and control; In each of them, the description, techniques, instruments, and validation are presented. Through an unstructured interview with customer service personnel and administrative staff, information was gathered to build a simulation model of the initial situation in the Arena 15.1 software. Then, three improvement alternatives were designed, and their results were compared with the original scenario, and it was concluded that the standardization of subprocesses and the hiring of additional personnel significantly improved the indicators. Furthermore, this study proposes to the educational management community a framework for evaluating and comprehensively improving customer service, along with five criteria for assessing customer service in this type of institution. However, it can be replicated in other organizations where customer service is relevant. Finally, although the impact of the proposals was meticulously measured through the Output Analyzer software, it would be even more accurate to analyze the consequences of the improvements if they were implemented in real life.